Correction: Broadband photoelectric tunable quantum dot based resistive random access memory. Issue 2 (6th January 2021) - Chen, Zhiliang; Yu, Yu; Jin, Lufan; Li, Yifan; Li, Qingyan; Li, Tengteng; Li, Jie; Zhao, Hongliang; Zhang, Yating; Dai, Haitao; Yao, Jianquan
Abstract : Correction for 'Broadband photoelectric tunable quantum dot based resistive random access memory' by Zhiliang Chen et al., J. Mater. Chem. C, 2020, 8, 2178–2185, DOI: ; 10.1039/C9TC06230K .